A few models, many discourses - Ugarte Calleja, S. (2017)
The austerity and grandeur in the design of some books, especially art catalogs, is primarily a visual and tactile pleasure that lasts over time. This paper proposes a classification of the different types of art catalogs as unique tools for the understanding of artwork. This classification is developed from the technical parameters and the tools of media publishing: typography, graphic design, photography. © Common Ground, Seber Ugarte Calleja, All Rights Reserved.